Funding and Service Organization to Achieve Universal Health Coverage for Medicines: An Economic Evaluation of the Best Investment and Service Organization for the Brazilian Scenario. - Garcia, Marina Morgado; Azevedo, Pamela Santos; Mirelman, Andrew; Safatle, Leandro Pinheiro; Iunes, Roberto; Bennie, Marion Clark; Godman, Brian; Guerra Junior, Augusto Afonso (Frontiers in Pharmacology, 2020)
The efforts of Brazil to achieve UHC for medicines resulted in increased medicines public finance and availability, reducing avoidable hospitalization and mortality. Family-income inequalities, insufficient funding, and suboptimal private sector–public sector collaboration are still areas for improvement. Thus, the lack of access health care remain and the scenario shows an even a lower access level comparing to the group of middle-income countries. Some developing countries finance and promote medicines access by using the public infrastructure of health care/medical units as dispensing sites and paying for each resource consumption up to the dispensing to the patient. In this study, we will undertake an economic evaluation to understand the funding needs of the Brazilian NHS to reduce inequalities in the access to medicines in a scenario of adopting a pharmaceutical services organization accrediting private pharmacies. We performed an economic evaluation of alternative model to provide access to medicines with public funds based on a decision tree: public pharmacies versus private pharmacies (NHS, agreements) in the perspective of the NHS. We performed a budget impact forecast to estimate the incremental funding needs to reduce inequalities in the access to medicines in Brazil. The model without price rebates for medicines estimated an incremental cost of 3.1 billion US dollars in purchasing power parity, but with an increase of availability of medicines from 65% to 90% for citizens across the country and all classes of family incomes. The value of annual medicines purchase places NHS in a position of negotiating rebates. Forecast scenarios above 35% rebates rank the alternative of hiring private pharmacies as dominant. Higher rebate rates are feasible and may lead to savings of more than 1.3 billion dollars per year (30%). The impact of incremental funding is related to medicines access improvement of 25% in the second year when paying by dispensing. The estimate of incremental budget in five years would be 4.8 billion USDPPP. We have yet to explore what would be the reduction in hospital and outpatient costs, as well as in lawsuits as the yearly expenses for the NHS are 9 billion and 1.4 billion USDPPP, respectively in 2017.